Kinerja Pegawai dalam Meningkatkan Pelayanan Administrasi Kependudukan di Desa Kalidawir Kecamatan Tanggulangin - Poernomo, Tasya Novitasari; Mursyidah, Lailul (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
Employee performance is a crucial aspect in performance appraisals for the sustainability of an organization to achieve its goals and realize a well-functioning public bureaucracy in service delivery, aiming to create quality and professional outcomes. This study seeks to understand the performance of employees in enhancing services in population administration, as it significantly influences the service activities within the government of Kalidawir Village, Tanggulangin Subdistrict. The research method employed is qualitative with a descriptive approach. Data is collected through interviews and observations involving relevant village officials. Subsequently, data is analyzed through data reduction, data presentation, and verification or conclusion. The study results indicate that employee performance in enhancing services in Kalidawir Village, Tanggulangin Subdistrict, can be considered quite good. However, there are still some challenges in implementing these services that need to be addressed, particularly concerning the complex and time-consuming nature of employee performance in administration, leading to a lack of comprehensive information, which hinders the effectiveness and efficiency of public services.